2017
DOI: 10.21649/akemu.v23i2.1576
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p63 Protein to Differentiate Benign Prostatic Hyperplasia and Carcinoma of Prostate in Pakistani Population

Abstract: Background:  Prostate cancer is the world’s foremost and second cause of cancer associated death typically in males after lung cancer. Histopathological diagnosis of prostatic hyperplasia and prostatic carcinoma can be challenging. The expression of p63 can be used in diagnosis and differentiation of benign pro-static hyperplasia from carcinoma of prostate.Materials and Methods:  We studied sixty prostatic biopsies obtained by TURP and radical prostatectomy. For each case, clinical data was collected. The tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…13 It was observed that all 25 (100%) cases of NHP showed positive p63 expression and all 25 cases of adenocarcinoma showed negative expression of p63 as a basal cell marker. The findings of the current study were similar with findings of Nisar et al and Kalantari et al 15,16…”
Section: Figure 1: Age Distribution Of Study Population (N=50)supporting
confidence: 93%
“…13 It was observed that all 25 (100%) cases of NHP showed positive p63 expression and all 25 cases of adenocarcinoma showed negative expression of p63 as a basal cell marker. The findings of the current study were similar with findings of Nisar et al and Kalantari et al 15,16…”
Section: Figure 1: Age Distribution Of Study Population (N=50)supporting
confidence: 93%
“…No study has not been conducted on NKX3. 14,15,16 Our research ndings coincide with research carried out in Sudan. Out of the 40 cases, Immunohistochemistry revealed loss of NKX3.1 expression in 26 cases of prostatic adenocarcinoma, whereas 14 cases showed positive expression.…”
Section: Discussionsupporting
confidence: 58%